Bandgap circuit design using current mode approach - Chow, Mei Yi. (2013)
The purpose of the circuit design is to design a Bandgap Circuit that is to design an operational amplifier (Op-amp) to be able to operate its function close to the idea of how an ideal operational amplifier (Op-amp). When choosing a suitable design to be implemented in the circuit, one have to understand the background analysis of how a equipment would operate. Thus, it is important to study the characteristics of each of the transistors used. In addition, by using the current mode approach, the required work down voltage for the circuit is lower than that of a voltage approach mode as the output is controlled by the current. With this, it is also essential to design a Bandgap circuit that is able to increase the output impedance to provide a large Op-amp gain. Therefore, there's a need to choose an appropriate Op-amp design and fulfill the requirements to fit the above description to have an optimal result.